Comparison of pre-emptive butorphanol or metamizole with ketamine +medetomidine and s-ketamine + medetomidine anaesthesia in improving intraoperative analgesia in mice. (October 2019) - Bauer, C; Schillinger, U; Brandl, J; Meyer-Lindenberg, A; Ott, A; Baumgartner, C
In accordance with the 'refinement' component of the 3Rs, the primary aim of this study was to investigate and compare ketamine + medetomidine (KM) and s-ketamine + medetomidine (SKM) anaesthetic protocols in C57BL/6J mice (both sexes). We sought to determine whether s-ketamine could provide adequate surgical tolerance at a 50% dose relative to that of ketamine racemate and whether antagonism of medetomidine could be initiated 15 min earlier. The second aim was to investigate the potential improvement in analgesia for both anaesthetic protocols by adding butorphanol or metamizole. Analgesia was tested via the pedal withdrawal reaction (PWR) to a painful stimulus. During anaesthesia, respiratory frequency, pulse oximetry, body temperature and PWR were monitored. Among the 16 mice in each group, the PWR was lost in all the KM + metamizole (35:56 ± 6:07 min), KM + butorphanol (43:45 ± 2:14 min) and SKM + butorphanol (24:03 ± 5:50 min) mice, 15 of the non-premedicated KM (37:00 ± 8:11 min) mice, and 9 of the pure SKM (20:00 ± 4:19 min) mice; the latter group increased to 11 mice (17:16 ± 5:10 min) with premedication of metamizole. In contrast to the racemic combination, s-ketamine at the dose used here did not lead to sufficient loss of the PWR. However, earlier partial antagonism of SKM resulted in a slightly shorter and qualitatively better recovery than later partial antagonism of SKM. The addition of metamizole or butorphanol to KM or SKM anaesthesia positively influences the analgesic quality. However, when butorphanol is added, controlled ventilation may be necessary, especially for male mice.